Women’s Social Status in Western and Arabic Novels “Al-Kafira” The Infidel Woman by Ali Bader and the Scarlet Letter by Nathaniel Hawthorne - Ali, Fouad Abbas; Saad, Haider Luaibi; Hussein, Dua'a Hafidh (International Journal of Psychosocial Rehabilitation, 2020)
This study aims at investigating women’s social status in western and Arabic novels “Al-Kafira” the Infidel Woman by Ali Bader and the Scarlet Letter by Nathaniel Hawthorne in different cultures and centuries. To approach the aim of the present study; the researcher invests an analytical method in order to describe the women’s social status in the Infidel Woman by Ali Bader and the Scarlet Letter by Nathaniel Hawthorne. However, this study has proven to be extremely women have found comfort in literature, particularly in novels, in pronouncing their life on earth and in announcing their resolution of liberty that enables them to express most of their thoughts and feelings. This study has defined the way the novels explores women’s suffering and how they try to solve difficulties and succeed.